Lasting Effects of Wildfire on Disinfection By‐Product Formation in Forest Catchments. Issue 6 (1st November 2019) - Chow, Alex T.; Tsai, Kuo‐Pei; Fegel, Timothy S.; Pierson, Derek N.; Rhoades, Charles C.
Abstract : Severe wildfires often have dramatic short‐term effects on water quality, although there is increasing evidence that in some catchments their effects can persist for many years. Forest recovery after the 2002 Hayman Fire burned catchments that supply drinking water to over a half million users in Denver, CO, has been extremely slow and has caused persistent water quality concerns. To evaluate whether postfire water quality changes increase the potential to form undesirable by‐products of water disinfection, we compared stream water from eight burned catchments within the Hayman Fire and five adjacent unburned catchments. We tested dissolved organic carbon (DOC) concentrations and the formation of disinfection by‐products (trihalomethanes [THMs], haloacetonitriles [HANs], chloral hydrate [CHD, and haloketones [HKTs]) in stream water monthly during 2014 and 2015. Stream DOC, THMs, and CHD and specific ultraviolet absorbance at 254 nm (SUVA254 ) were elevated in catchments with a moderate extent of high‐severity wildfire (8–46% of catchment area) relative to catchments that were unburned and those that burned more extensively (>74% of catchment area) 14 yr after the fire. In contrast, formation of highly toxic but unregulated nitrogenous HANs increased linearly with wildfire extent. Although these findings should not raise concern regarding drinking water safety, they highlight the long‐term influences of high severity wildfire on source water C content, composition, and treatability. Core Ideas: Wildfire impacts on source water quality could last over a decade. Formation of highly toxic nitrogenous DBP precursors increased linearly with wildfire extent. DBP formation was highest in streams draining moderately burned catchments.